DRESS syndrome after short-time exposure to ciprofloxacin - Meneses, Giovanni (2022)
A 38-year-old woman with an initial diagnosis of urinary tract infection (UTI) was treated for five days with ciprofloxacin. On the third day of treatment, she presented fever, eyelid edema and rash over 50% of the body associated with pruritus. On admission, ceftriaxone was started considering a complicated UTI. On the eighth day, eosinophilia was evidenced and DRESS syndrome was diagnosed, being treated with chlorphenamine and ranitidine, achieving progressive remission of the initial symptoms.